Response of alectra vogelii benth to different crop root exudates - Njekete, Cliven; Midzi, Joanah; Ncube, Bhekumthetho; Madanzi, Tendai (SCIENCEDOMAIN International, 2018)
Aims: The aim of the study was to evaluate the effect of root exudates from cowpea, groundnut, maize, sorghum and pearl millet genotypes on the germination and attachment of Alectra vogelii. It also aimed to identify functional groups in the powdered root samples that stimulate A. vogelli germination.